THE GIVING OF GINGER FLOUR (ZINGIBER OFFICINALE) AND TURMERIC FLOUR (CURCUMA DOMESTICA) ON COMMERCIAL FEED TO QUAIL (COTURNIX COTURNOC JAPONICA) PERFORMANCE OF LAYER - Bashar, Septiar; Nur, Hanafi; Sudrajat, Deden (Universitas Djuanda Bogor, 2017)
The quail is one kind of poultries that can give the distribution of society interests in case of eggs providing. There are kinds of research that related to feed aspect, one of them is the way to increase the quality of feed by adding ginger flour and turmeric flour on commercial feed. The aim of this research is to review the influences of giving the ginger flour (Zinger officinale) and turmeric flour (Curcuma domestica) on commercial feed toward quail performance (cortunix cortunix japonica) in layer period. Complete randomized design with used by the following treatment: P0 (commercial feeding without ginger flour and turmeric flour), P1 (commercial feeding with 1% ginger flour), P2 (commercial feeding with 1% turmeric flour), and P3 (feed commercial with 0.5% ginger flour and 0.5% turmeric flour). The treatment was conducted to quail aged 35 days until 67 days old. The feed and drink was given by adlibitium (always available). Giving ginger flour and turmeric flour does not affect the feed consumption, egg’s weight, feed convertion, depletion, and the production of quail’s egg in layer period, however, by adding 1% ginger on rations that is used, it can improve the convertion in the amount of 12.4% and increase the producing of egg in the amount of 19.9%.Key words : Quail performance of layer period, ginger flour, turmeric flour, commercial feed